2019
DOI: 10.1053/j.jvca.2018.08.190
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary-Systemic Pressure Ratio Correlates with Morbidity in Cardiac Valve Surgery

Abstract: The pulmonary-systemic ratio is more strongly associated with risk-adjusted morbidity and mortality in valve surgery than pulmonary arterial pressure. By integrating ventricular interactions, this metric may better characterize the risk of valve surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 17 publications
0
9
0
Order By: Relevance
“…21 Unfavorable ventricular-ventricular interactions as reflected by a high mean arterial pressure to mPAP ratio have also been associated with increased morbidity and mortality among patients undergoing valvular heart surgery. 8 Specifically, right ventricular function has been shown to be an important prognostic indicator for patients with various cardiac conditions including those undergoing surgery. 22,23 CVP, a proxy for right ventricular function, reflects the right ventricular preload and by extension marks the right ventricular contractile response to afterload imposed on it.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…21 Unfavorable ventricular-ventricular interactions as reflected by a high mean arterial pressure to mPAP ratio have also been associated with increased morbidity and mortality among patients undergoing valvular heart surgery. 8 Specifically, right ventricular function has been shown to be an important prognostic indicator for patients with various cardiac conditions including those undergoing surgery. 22,23 CVP, a proxy for right ventricular function, reflects the right ventricular preload and by extension marks the right ventricular contractile response to afterload imposed on it.…”
Section: Discussionmentioning
confidence: 99%
“…At the authors' institution, an estimated 11.6% of all valvular surgery patients undergo preoperative right heart catheterization. 8…”
Section: Measurements and Data Handlingmentioning
confidence: 99%
“…In recent years, NO inhalation therapy has been used in adults who have undergone cardiac surgery [4][5][6]. Some patients who undergo cardiac valve surgery develop PH postoperatively [7]; therefore, as postoperative PH portends worse outcomes, research and use of NO inhalation therapy in adult patients have attracted attention. However, evidence of improved outcomes with the use of NO in adults with PH after mitral valve surgery is insu cient.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the complexity of PH in left heart disease is apparent and different mechanisms may be contributing to its occurrence, which are determined largely by the nature of lesion, for example, primary mitral valve disease (stenosis or regurgitation), secondary MR, AS, and heart failure with preserved ejection fraction. The results of Schubert and colleagues' study 7 must be interpreted in light of this and offer the following learning points.…”
mentioning
confidence: 99%
“…5,6 In this issue of the Journal of Cardiothoracic and Vascular Anesthesia, Schubert and colleagues have published a report on 314 patients with PH undergoing valve surgery with or without coronary artery bypass grafting. 7 The authors have used a pulmonary-systemic ratio (mean pulmonary artery pressure [MPAP]/mean systemic artery pressure [MAP] to predict the worse outcome after surgery. In this group of patients predominantly composed of those undergoing aortic valve surgery, the authors found that patients with the highest pulmonary-systemic ratio had the highest rates of morbidity and mortality.…”
mentioning
confidence: 99%